Participation of Women With Disabilities in Government Poverty Reduction Programmmes in Kanyum Sub-county, Kumi District - Amongin Lona Edongot (Uganda Christian University, 2025)
The purpose of the study was to investigate the participation of women with disabilities in Government poverty eradication programmes in Kumi Sub-County, Kanyum District The specific objectives of the study were; to find out the existing Government poverty eradication programmes in Kanyum Sub-County, the level of participation of women with disabilities in Government poverty eradication programmes and the challenges faced by women with disabilities while participating in Government poverty eradication programmes. The study used a descriptive research design with a qualitative approach and it employed purposive sampling technique. A total of 25 participants were involved in the study and these included; 20 persons with disabilities, 1 CDO and 4 local leaders. A semi-structured interview guide was used collect information from participants. The study revealed that the existing government poverty eradication programmes in Kanyum SubCounty are; Parish development models, Special Grant to persons with disabilities, Women Entrepreneurship Programme (UWEP) and Social Assistance GrantforEmpowerment (SAGE). The study further revealed that the participation of women with disabilities in Government poverty eradication programs is very low in Kanyum Sub-County. Majority of Participants stated that very few of them take part in government poverty eradication programmes. It was established that the major challenges experienced by women with disabilities while participating in Government poverty eradication programs include; unmodified environment, negative attitudes towards women with disabilities by ordinary people and implementers of government eradication programmes, too much requirements for one to engage in the programme and programmatic factors such as scheduling of activities in inconvenient time and places were that. The recommendations that came out of the of the study were; sensitization of WWDs about Government poverty eradication programmes, training implementers of Government poverty eradication how to handle WWDs, modification of the environment in all public facilities so that WWDs can easily access all the places including those where poverty eradication programmes are conducted from and WWDs should form groups in order to benefit from poverty eradication programmes.